2005
DOI: 10.1017/s0950268805004437
|View full text |Cite
|
Sign up to set email alerts
|

Rubella and measles seroprevalence among women of childbearing age, Argentina, 2002

Abstract: To assess rubella and measles susceptibility among women of childbearing age we conducted a cross-sectional seroprevalence study in four cities and one rural area in Argentina. A convenience sample of women aged 15-49 years seeking care in public health-care institutions was selected (n=2804). Serum specimens were tested for rubella and measles IgG antibody titres. The overall susceptibility to rubella and measles was 8.8 and 12.5% respectively. Seroprevalence differences were found for both rubella (P<0.001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
6
13
1
2
Order By: Relevance
“…Our multivariate analysis supported no association of parity or maternal educational status with rubella susceptibility, which is consistent with findings elsewhere [23][24][25][26]. Apparent association on univariate analysis was probably due to increased maternal age as a confounding factor, although there might be a potential risk of transmission from elder siblings to mothers.…”
Section: Discussionsupporting
confidence: 91%
“…Our multivariate analysis supported no association of parity or maternal educational status with rubella susceptibility, which is consistent with findings elsewhere [23][24][25][26]. Apparent association on univariate analysis was probably due to increased maternal age as a confounding factor, although there might be a potential risk of transmission from elder siblings to mothers.…”
Section: Discussionsupporting
confidence: 91%
“…Até o final da década de 1980 era desconhecida a verdadeira magnitude da rubéola na maior parte dos países da América Latina, incluindo o Brasil. Nos últimos anos, estudos de soroprevalência vem sendo realizados em alguns grupos populacionais, cujos resultados vêm norteando a definição e a implementação de estratégias de vacinação 4,5,6,7,8 . …”
Section: Introductionunclassified
“…Rubella IgG seropositivity rate increased with increasing age, but it was not statistically significant. Studies by Dayan et al (18) and Palihawadana et al (19) found significant increasing seroprevalence of rubella with increasing age. A study by Pehlivan et al (20) among Turkish women however, reported no significant relationship between age and rubella seroprevalence.…”
Section: Discussionmentioning
confidence: 91%
“…Low avidity rubella IgG antibodies were significantly more in younger age group than older age group (P = .001). The group with low avidity IgG are at risk of a reinfection which carries a low (8%) risk for having children with CRS (18). It may also indicate recent rubella infections in 11.9% participants which are in their reproductive age.…”
Section: Discussionmentioning
confidence: 99%